Sustainability of traditional medical knowledge among Semaq Beri tribe in Hulu Terengganu. - Mohamad Hafis, A.S.; Ramle, A.; Nurul Faezah, N.A.; Norhayati, A.M. (2016)
Semaq Beri community in the State of Terengganu is one of the aboriginal tribes that still use natural resources to fulfill the daily necessities such as food, equipment and also use for health care. This practice was a traditional knowledge that very useful and should be maintained. This study was conducted to see the process of enculturation in the field of medical practice by the Semaq Beri community with the question: i) How does the process of inheritance of medical knowledge based on the use of natural resources is carried out? ii) What are the criteria required by the next generation in the succession of medical knowledge? The study was carried out by conducting field work for 7 months starting from August 2015 until February 2016. During the fieldwork, data were collected through observation and in-depth interview technique involves three main informants which is a traditional medical practitioner. The results showed that the succession process knowledge to the new generation either by using a source of flora or fauna have occurred directly and indirectly. This process involves practitioners, delivery and heir. Based on these results, traditional knowledge regarding the use of natural resources as an ingredient in their health care will continue to be sustainable in their communities as long as the process of inheritance this knowledge occurred.